Lenalidomide plus rituximab (R2) in previously untreated marginal zone lymphoma: subgroup analysis and long‐term follow‐up of an open‐label phase 2 trial. (28th March 2019) - Becnel, Melody R.; Nastoupil, Loretta J.; Samaniego, Felipe; Davis, Richard E.; You, M. J.; Green, Michael; Hagemeister, Fredrick B.; Fanale, Michelle A.; Fayad, Luis E.; Westin, Jason R.; Wang, Michael; Oki, Yasuhiro; et al.
Summary: Lack of consensus for first‐line marginal zone lymphoma (MZL) treatment and toxicities associated with currently available systemic therapies have inspired evaluation of immunotherapeutic agents yielding robust outcomes with improved tolerability. We previously reported durable efficacy with first‐line lenalidomide and rituximab (R 2 ) in follicular lymphoma, MZL and small lymphocytic lymphoma with a subsequent long‐term follow‐up shown here in MZL patients. This phase 2 investigator‐initiated study included previously untreated, stage III/IV MZL patients treated with lenalidomide 20 mg/day on days 1–21 and rituximab 375 mg/m 2 on day 1 of each 28‐day cycle, continuing in responders for ≥6–12 cycles. The primary endpoint was overall response rate (ORR); secondary endpoints were complete and partial response (CR, PR), safety, and progression‐free survival (PFS). The ORR was 93% with 70% attaining CR/CR unconfirmed. At median follow‐up of 75·1 months, median PFS was 59·8 months and 5‐year OS was 96%. Most non‐haematological adverse events (AE) were grade 1/2. Grade 3 haematological AEs were neutropenia (33%) and leucopenia (7%), and grade 4 were leucopenia (3%) and thrombocytopenia (3%). Two patients died of secondary malignancies; no treatment‐related fatalities occurred. With extended follow‐up, outcomes for MZL patients receiving R 2 were robust with no unexpected late or delayed toxicities.